Mass spectral behaviour of some octahydro-1,3- and -3,1-benzoxazines with a heteroaryl-substituted phenyl substituent at ring position 2+ - Vainiotalo Pirjo; Forró Enikő; Fülöp Ferenc (1998)
The 70 eV mass spectra of tell octahydro-1,3- and -3,:-benzoxazines with a heteroaryl-substituted phenyl group at ring position 2 were recorded in order to establish the effects of heteroaryl substituents on the fragmentation patterns. The 1,3- and -3,1-benzoxazine derivatives were easy to differentiate. The structure of the heteroaryl substituent likewise had a surprisingly large effect on the fragmentation behaviour of the compounds, in particular, the 1,2,3-benzotriazolyl group prompted fragmentation pathways that were totally absent for other isomers. All the compounds studied existed almost completely in the ring form in the gas phase. However, it was not possible to determine the exact position of the equilibrium because of the presence of the many fragment ions, some of which could originate from either tautomeric form.
Keywords: Klinikai orvostan